Hubungan Skala Usaha dan Efisiensi Pengelolaan Keuangan pada KSP Makmur Mandiri - Bernad Adi Juang Eho Giawa; enik rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the relationship between business scale and financial management efficiency at KSP Makmur Mandiri, Semarang Regency. The problem focuses on how the growth in membership, assets, and financing volume affects governance effectiveness and financial performance. The study employs theories of business scale, organisational efficiency, and cooperative governance. Data were collected through in-depth interviews with board members, managers, and cooperative members, along with financial document analysis, and were examined using thematic analysis. The findings reveal that: (1) business scale growth drives administrative system improvement and digitalisation of financial records; (2) financial efficiency improves through better cost control and fund circulation; and (3) strengthened internal supervision is a key factor in maintaining financial stability. This study concludes that business scale positively contributes to financial management efficiency, but the relationship depends on managerial readiness and adaptive governance. This research contributes by providing a qualitative perspective on cooperative efficiency at the local level.